Prevalence and incidence of balance disorders in community-dwelling older adults: Protocol for the EPIBAS epidemiological balance study - Pilar Montero-Alía; Antonia Fornes-Reynes; M. Carmen Rodríguez-Pérez; Rosalía Dacosta-Aguayo; Ramón Miralles-Basseda; Tamara Jiménez-Pascua; Jofre Pascual-Bielsa; M. José Durá Mata; M. Mercedes Molleda-Marzo; Lucía Ramos-García; Víctor M. López-Linfante; Maria Doladé-Botías; et al. (PLoS ONE, 2026)
Background Poor balance leads to falls, which can cause a loss of personal autonomy and reduced quality of life. Epidemiological studies of balance disorders (BDs) are limited. Identifying their prevalence and accessible diagnostic markers is crucial for prevention and monitoring. Aims 1) Assess the prevalence of BDs in men and women aged 65–72 using posturography and different balance tests, and track the annual incidence of BD; 2) Analyze the association between retinal microvasculature abnormalities and BD; 3) Evaluate the effectiveness of the Wii Balance Board™ for balance assessments compared to posturography; 4) Explore whether knee extensor strength and a combined measure of physical and cognitive function can serve as predictors for BD and fall risk: and 5) Conduct an external validation of the Health Assessment Tool (HAT) in the Spanish population. Methods Two-phase, observationals study. Phase I: Descriptive, cross-sectional. Phase II: Follow-up of cohorts at 18 months. Sample: 1,316 people aged 65–75 residing in Mataró (Barcelona, Spain) shall be included in the study, excluding individuals who cannot walk independently. They shall undergo posturography, retinal photography, knee extensor strength assessment, as well as the Tinetti Test, Timed Up and Go test, Unipedal stance test, Short Physical Performance Battery (SPPB), and balance assessment using the Nintendo Wii at baseline and at the end of the follow-up period. Bimonthly phone calls shall be made to detect the occurrence of falls. Applicability and relevance BDs are underdiagnosed and under-treated, and current awareness only scratches the surface. Expanding knowledge in this field is essential to avoid the loss of functional autonomy in individuals. Doing so will make it possible to develop specific preventive measures for the population at greatest risk of falls, thus making the approach to this significant geriatric syndrome more efficient. The EPIBAS study is registered on Clinicaltrials.gov under the code NCT06965660.